EFEKTIVITAS, FEASIBILITAS DAN AKSEPTABILITAS METODE PEMBELAJARAN FLIPPED CLASSROOM DI BIDANG KEDOKTERAN - Pariartha, I Made; Putra, Adi Pratama; Ekayani, Ni Wayan Diana (PendIPA Journal of Science Education, 2024)
Flipped classroom (FC) have advantages compared with traditional lectures. One of them is the occurrence of active learning.  This study aims to assess the flipped classroom learning method's effectiveness, feasibility and acceptability. Research method with mixed method. Quantitative method with pre-test and post-test control group design. One with traditional lecture (TL) and another with the flipped classroom method. Effectiveness was assessed by pre-test and post-test. The post test was carried out on day 0, 3, 7 and 14. FGD assessed the feasibility and acceptability of FC. TL are in pregnancy physiology courses, while FC are in labor physiology courses. There were differences in pretest scores in the FC group compared to TL, 4.89 (± 0.85) vs 4.29 (±1.01) (p=0.000), respectively. There were differences in posttest scores d-0, d-3, d-7, d-14 between the FC group and TL group, 7.89 (± 0.85) vs 7.29 (±1.01) (p = 0.000); 6.82 (± 0.78) vs 6.14 (±0.81) (p= 0.000); 5.85 (± 0.80) vs 5.20 (±0.88) (p= 0.000); 5.81 (± 0.77) vs 4.78 (±0.82) (p= 0.000), respectively. FC are difficult, burdened students, stimulate more active learning, are not suitable for certain learning, and provide an overview of real situations. Flipped classroom is more effective than traditional lectures. Flipped classroom can be applied (feasible) in teaching medicine, but the acceptability of this method still varies.